Severe group A streptococcal infections in a paediatric intensive care unit. (9th June 2014) - Lithgow, Anna; Duke, Trevor; Steer, Andrew; Smeesters, Pierre Robert
<x xml:space="preserve">Abstract</x> Aim To describe the clinical presentation, management and outcomes for children with invasive group A streptococcal (GAS) infection in a paediatric intensive care unit (PICU). Methods We reviewed the clinical and laboratory records of patients admitted to a PICU in Melbourne with invasive GAS infection from April 2010 to April 2013. Outcomes recorded included survival, organ failure, need for extracorporeal support, renal replacement therapy and prolonged neuromuscular weakness. Results Twelve cases of invasive GAS infection were identified. The most common clinical presentations were pneumonia (n = 5), bacteraemia with no septic focus (n = 4) and septic arthritis (n = 3). Necrotising fasciitis occurred in one patient and another patient presented with ischaemic lower limbs requiring amputation. Of the eight isolates with available emm typing results, the most common emm type was emm1 (n = 4) followed by emm4, 12 and 22. Nine patients had multi‐organ failure. Ten patients required mechanical ventilation for a median duration of 8 days. Nine patients required inotropic and/or vasopressor support and four patients extracorporeal membrane oxygenation support. Eleven patients survived. A prolonged period of neuromuscular weakness following the initial severe illness was common (n = 5), but most children returned to normal or near normal neurological function. Conclusions Invasive GAS disease in children may cause severe multi‐organ failure with resultant prolonged intensive care stay and significant morbidity. However, a high rate of survival and return to normal functioning may be achieved with multi‐system intensive care support and multi‐disciplinary rehabilitation.